(3JQHjI GdeDefjf aj JChjd OYGFe GdESdGes - (3GHf nMoqjhf; GdfYeGf Hf eMeO Hf efUhQ, CHh MfjaI Hf Mjhf GdJejej, hjbGd dg GdbGVj GdfYeGf,J (B363 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNQL GdhO b hebOQ GdQRb hNGdb GdYHGO ai HWhf GegGJge NdbkG HYO Ndb CjgG GdeDefjf ajeG JbOe cja GfJe Jfbdhf MGdkG HYO MGd s
(3BNQgG (B:s
(3hGYedhG ceG GeQce Gddg XGgQkG hHGWfkG hSQkG hYdGfjI GYGfce Gddg Ydi GbGeI hRGOce ef aVdI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs